Teachers’ Challenges in Designing Worksheet for Differentiated Learning in Merdeka Curriculum - Rahma, Alifia; Madjid, Hilda Izzati; Rofiq, Ainur (ICONELT, 2024)
In the context of Indonesia's Merdeka Curriculum, which emphasizes personalized and student-centered learning, teachers face significant challenges in designing worksheets that cater to diverse learning needs. This article explores the complexities encountered by educators when creating differentiated worksheets within the framework of the Merdeka Curriculum. Through interviewing English teachers at one of islamic senior high schools in Sidoarjo, the data related to the challenges that the teachers encounter in designing differentiated learning worksheets are explored. The challenges include balancing curriculum standards with individual learning styles, ensuring equitable access to resources, and adapting instructional materials to varying levels of student ability. Furthermore, the study highlights the critical need for professional development and support systems to enhance the teachers’ capacity in designing worksheets within the context of the Indonesian curriculum framework. By addressing these challenges, the Merdeka Curriculum's goal of fostering inclusive and effective learning environments can be more fully realized, ultimately supporting improved educational outcomes for all students.